Metformin Inhibits Advanced Glycation End Products (AGEs)-induced Renal Tubular Cell Injury by Suppressing Reactive Oxygen Species Generation via Reducing Receptor for AGEs (RAGE) Expression - Ishibashi, Y.; Matsui, T.; Takeuchi, M.; Yamagishi, S. (Hormone and Metabolic Research, 2012)
Advanced glycation end products (AGEs) and their receptor (RAGE) play a role in tubulointerstitial damage in diabetic nephropathy. Recently, metformin has been shown to ameliorate tubular injury both in cell culture and diabetic animal model. However, effects of metformin on AGEs-induced tubular cell apoptosis and damage remain unknown. We examined here whether and how metformin could block the AGEs-RAGE-elicited tubular cell injury in vitro. Gene expression level was evaluated by real-time reverse-transcription polymerase chain reactions. Reactive oxygen species (ROS) generation was measured with dihydroethidium staining. Apoptosis was evaluated by DNA fragmentation and annexin V expression level. AGEs upregulated RAGE mRNA levels and subsequently increased ROS generation and intercellular adhesion molecule-1, monocyte chemoattractant protein-1 and transforming growth factor-β gene expression in human renal proximal tubular cells, all of which were significantly blocked by the treatment of 0.01 and 0.1 mM metformin. Compound C, an inhibitor of AMP-activated protein kinase significantly blocked the effects of metformin on RAGE gene expression and ROS generation in AGEs-exposed tubular cells. Furthermore, metformin dose-dependently inhibited the AGEs-induced apoptotic cell death of tubular cells; 1 mM metformin completely suppressed the pro-apoptotic effects of AGEs in 2 different assay systems. Our present study suggests that metformin could inhibit the AGEs-induced apoptosis and inflammatory and fibrotic reactions in tubular cells probably by reducing ROS generation via suppression of RAGE expression through AMP-activated protein kinase activation. Metformin may protect against tubular cell injury in diabetic nephropathy by blocking the AGEs-RAGE-ROS axis.
Keywords: AGEs; RAGE; metformin; diabetic nephropathy; ROS